2022
DOI: 10.3389/fonc.2022.1034397
|View full text |Cite
|
Sign up to set email alerts
|

Combining metformin with lactate transport inhibitors as a treatment modality for cancer - recommendation proposal

Abstract: Highly glycolytic cancer cells excrete lactate to maintain cellular homeostasis. Inhibiting lactate export by pharmacological targeting of plasma membrane lactate transporters is being pursued as an anti-cancer therapy. Work from many laboratories show that the simultaneous inhibition of lactate export and mitochondrial respiration elicits strong synthetic lethality. The mitochondrial inhibitor, metformin, has been the subject of numerous clinical trials as an anti-cancer agent. We propose that, in future clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this case, VB124, an MCT4 inhibitor, had antitumor effect, and the combination of AZD3965 and VB124 sensitized the killing by metformin 31 . Consequently, the simultaneous inhibition of MCTs and mitochondrial respiration has strong fatal effects against tumor cells 32 . This study revealed that the classical MCTs non-selective inhibitor CHC suppressed the viability of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, VB124, an MCT4 inhibitor, had antitumor effect, and the combination of AZD3965 and VB124 sensitized the killing by metformin 31 . Consequently, the simultaneous inhibition of MCTs and mitochondrial respiration has strong fatal effects against tumor cells 32 . This study revealed that the classical MCTs non-selective inhibitor CHC suppressed the viability of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, one of us (Koltai T) proposed the double approach of increasing intracellular lactate production by inhibiting complex I in the electron transport chain, with metformin and simultaneously inhibiting lactate extrusion [ 197 ]. This theoretical idea was further developed by other authors [ 198 ] and was proposed by Benjamin and Hall [ 199 ] to be used with AZD3965 acting as a lactic acid extrusion inhibitor. By itself, to have a significant effect AZD3965 may require doses that are toxic, and results are poor.…”
Section: Mct Inhibitorsmentioning
confidence: 99%